Respuestas

  • Usuario de Brainly
2013-05-08T08:32:51+02:00

supongo que f(x) = ax+b

entonces

 

y = ax + b                   x=1    y= 5 → 5 = a.1 + b → 5 - b = a

                                   x =3    y = 8 →8 =a.3 + b → resolvemos  sustituyendo a

                                                            8 = (5-b) . 3 + b

                                                            8 = 15 - 3b + b

                                                   8 - 15 =  - 2b

                                                       -7   =  - 2b

                                                    -7/-2 = b    →   7/2  = b 

 

entonces  a = 5 - b  → a = 5 -  7/2 → a = 3/2 

 

y = 3/2x + 7/2

 

espero que te sirva, salu2!!!!